Community Restorative Healing Project, Los Angeles, California, 2017-2018 - Dierkhising, Carly ([Verlag nicht ermittelbar], 2020)
The vision of the Community Restorative (CORE) Health Project was to increase awareness and availability of trauma-informed care and indigenous healing practices in the target communities for clients and families being served by the City of Los Angeles Mayor's Office of Gang Reduction and Youth Development (GRYD). Two agencies were contracted to provide either trauma-focused mental health treatment or training on indigenous healing practices to clients, families, and the community. A total of 115 individual or group therapy sessions were provided, 23 community based workshops on trauma-informed care or indigenous healing practices were offered, and 15 professional development events were attended by over 354 GRYD intervention workers or CORE staff. Background information was collected during the initial stages of the GRYD program, and a youth's eligibility for GRYD services was determined. The Posttraumatic Screening Inventory was used to assess the presence of posttraumatic stress, exposure to a traumatic event, and whether participants should be referred for treatment. Youths were then exposed to the GRYD's Summer Night Lights program, which raised trauma awareness, taught coping strategies, and increased access to services. Then the National Compadres Network was chosen to administer three training sessions on indigenous healing practices: La Cultura Cura, El Joven Noble, and Circle Keepers. Pre-test surveys collected demographics such as age, gender, ethnicity, and religiosity, as well as their expectations heading into training. Post-test surveys assessed how much information participants received, the usefulness of information, if training rationale made sense, and whether or not participants planned to use what they had learned. After training sessions were completed, researchers conducted 10 follow up interviews with services providers and leadership from CORE.